Glycyrrhetinic Acid Protects Renal Tubular Cells against Oxidative Injury via Reciprocal Regulation of JNK-Connexin 43-Thioredoxin 1 Signaling - Zhou, Yao; Gao, Leiping; Xia, Ping; Zhao, Jing; Li, Wei; Zhou, Yufeng; Wei, Qingxue; Wu, Qijing; Wu, Qi; Sun, Dongdong; Gao, Kun (Frontiers in Pharmacology, 2021)
Background and objective: The incidence of chronic kidney disease (CKD) is steadily increasing. Although renal tubular epithelium injury is closely correlated with the prognosis of CKD, the underlying mechanism is not fully understood and therapeutic strategies are limited. The main bioactive component of the Chinese medicine herb, glycyrrhiza, is 18α-glycyrrhetinic acid (Ga), which is also a pharmacological inhibitor of gap junctions. Our previous studies indicated that Ga is able to ameliorate renal cell injury. The present study explored the regulatory role of Ga in redox signaling in renal tubular epithelial cells with oxidative injury. Methods: Rat renal tubular epithelial cells, NRK-52E, were incubated with Px-12, a thioredoxin inhibitor, to mimic thioredoxin deficiency and induce oxidative injury in vitro. A Cell Counting Kit-8 was used to analyze cell viability while a reactive oxygen species (ROS)/superoxide (O2-) fluorescence probe was employed to determine oxidative stress. Apoptosis was evaluated using DT-mediated dUTP nick end labeling /4,6-diamidino-2-phenylindole staining and cleaved caspase 3 protein analysis. Western blot analysis was used to analyze the expression of specific proteins while siRNA transfection was performed to downregulate targeted proteins. Results: Inhibition of thioredoxin 1 by Px-12 triggered renal tubular cell oxidative injury as evidenced by morphological change, loss of cellular viability, over production of ROS and O2-, and appearance of cleaved caspase-3. Ga significantly attenuated cell oxidative injury, as indicated by the parameters mentioned above. Px-12 induced phosphorylation of c-Jun N-terminal kinase (JNK) and subsequently the expression of connexin 43 (Cx43) in NRK-52E cells. Ga and the JNK inhibitor, sp600125, markedly suppressed Px-12-induced generation of intracellular ROS and O2-. Inhibition of JNK improved Px-12-elicited NRK-52E cell injury. Moreover, sp600125 inhibited Cx43 expression. After downregulation of Cx43 via Cx43 siRNA transfection, the phosphorylation of JNK was markedly reduced. Furthermore, Ga restored the expression of thioredoxin 1 inhibited by Px-12. Conclusion: ROS-JNK-Cx43-thioredoxin 1 signaling plays a crucial role in renal tubular cell injury. JNK is involved in the regulation of thioredoxin 1 and Cx43, and Cx43 reciprocally regulates thioredoxin 1. Inhibition of gap junctions by Ga alleviated renal tubular oxidative injury via improvement of thioredoxin 1-mediated redox signaling.